Techno-economic analysis of solar integrated hydrothermal liquefaction of microalgae. (15th March 2016) - Pearce, Matthew; Shemfe, Mobolaji; Sansom, Christopher
Highlights: Hydrothermal liquefaction and concentrated solar power provide integrated biofuel technology. Heat kinetics and energy efficiency Aspen plus modelling of CSP and HTL. Microalgae biofuel minimum fuel sales price of $1.23/kg. Abstract: Integration of Hydrothermal Liquefaction (HTL) of microalgae biomass with concentrated solar power thermal processing (CSP) for bio-oil production is a potential processing pathway for energy efficient generation of renewable biofuels. Solar HTL infrastructure avoids additional bolt-on components of conventional solar parabolic trough systems used for electricity production including heat transfer fluids, counter current heat exchangers, fluid transfer interconnectivity and electrical power control systems. The absence of such capital intensive additional equipment considerably reduces the production costs of solar HTL biofuels compared to electricity generation from conventional CSP power systems. An economic and market appraisal of variance and system economic resilience is presented. It is hypothesised that the combination of nutrient recycling with HTL/CSP unification has the potential for economically sustainable microalgae bio-oil production. A microalgae biofuel minimum fuel sales price of $1.23/kg has been modelled. Further experimental work would be able to validate this integrated model.